(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Teaching Legal English to non-native speakers requires innovative methods to bridge linguistic proficiency with legal reasoning. This study explores the integration of case law from international jurisdictions—specifically the International Court of Justice (ICJ), International Criminal Court (ICC), European Court of Human Rights (ECHR), and World Trade Organization Dispute Settlement Body (WTO DSB)—into Legal English curricula. By employing case briefs, lexical analysis of judicial terminology (e.g., plaintiff, respondent, jurisdiction, ruling, appeal), and argumentative writing tasks (memoranda and position papers), the approach aims to enhance students’ linguistic and analytical skills. A 12-week course was implemented with 20 law students (B2–C1 CEFR levels) at a European university, using qualitative methods including curriculum design, corpus-based lexical analysis, and pre-/post-assessments. Results showed significant improvements: vocabulary accuracy rose from 45% to 82%, reading comprehension of case briefs improved by 25%, and argumentative writing gained clarity and precision. Students reported increased engagement and confidence in discussing international law. Challenges included initial difficulties with judicial texts, addressed through scaffolding. The study suggests that case law integration fosters interdisciplinary learning, preparing students for global legal practice. Future research could explore digital tools for case preparation or broader proficiency ranges. This approach offers a scalable model for Legal English instruction, blending language acquisition with practical legal insight.